Improving SME Business Models through Sustainable Development: A Case Study of X sp. z o.o., Poland - Katarzyna CHŁAPEK; Sylwia KRAJEWSKA; Bozena GUZIANA (Communications of International Proceedings, 2023)
At a time of crisis related to the COVID 19 pandemic and the conflict in Ukraine, there is a need to re-examine the business model and include sustainable development as a key element. This also applies to SMEs.  The sector faces many difficulties that limit its ability to implement innovative solutions that enable continuous development. Despite the threats and difficulties, this sector is extremely important for the economy, not only in Poland, but all over the world. SME contribute significantly to GDP creation, the number of jobs available, and the level of investment outlays. The aim of the article is an attempt to construct a business model for enterprises and SMEs based on the assumptions of The Triple Layered Business Model Canvas (TLBMC). The basic research methods used to achieve this goal are case studies and critical literature studies, and in formulating conclusions – methods of deduction and synthesis. The results of the conducted research indicate that it is possible to use the modified TLBMC model in constructing a business model of an entity from the SME sector, considering the need to adapt it to the specifics of this sector.
Keywords: Business model; Agenda 2030; ESG; SME; The Triple Layered Business Model Canvas (TLBMC)